Immune checkpoint inhibitor‐induced diarrhea: Clinicopathological study of 11 patients. Issue 4 (12th November 2019) - Yanai, Shunichi; Nakamura, Shotaro; Kawasaki, Keisuke; Toya, Yosuke; Akasaka, Risaburo; Oizumi, Tomofumi; Ishida, Kazuyuki; Sugai, Tamotsu; Matsumoto, Takayuki
Abstract : We reviewed the records of patients with immune checkpoint inhibitor (ICI)‐induced diarrhea during 2015 to 2019. ICI included nivolumab and ipilimumab. There were 11 patients with ICI‐induced diarrhea aged 46–81 years (median, 63 years). On colonoscopy, four patients appeared normal, whereas loss of vascularity, erythema, granularity, erosions or ulcerations apparently mimicking ulcerative colitis were found in seven patients. Those seven patients had acute inflammation, cryptitis, crypt abscess and apoptosis, suggestive of ICI‐induced colitis. Five of the seven patients were treated with prednisolone, two of whom were resistant to prednisolone and required infliximab. In contrast, none of the four patients without ICI‐induced colitis required further treatment. Our observations suggest that diversity exists in the clinical, endoscopic and histological severity of patients with ICI‐induced diarrhea. Colonoscopy together with biopsy is inevitable for the diagnosis of ICI‐induced colitis, which requires intensive treatment.